PERAN IMF MENGATASI KRISIS FINANSIAL SPANYOL - Fiqhri Hidayat; Pazli " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research explains about economic crisis in Spain. The discuscion is focused on dimention of IMF’s role in facing Spain’s economic crisis by creating program that started in 2012. European Union crisis is first started in grEece and followed by few other countries such as Portugese, Ireland and including Spain which is started from economic bubble effect. To decrease the crisis, Spain has proposed bailout from Eurpean Union that join with IMF as the monitorer and advisor to Spain government facing the economic crisis esspecially in banking which is the main proble in this country.Keywords: IMF, Spain, EU, Economic Crisis